Cormocephalus (Cormocephalus) guildingii Newport, 1845 (Chilopoda: Scolopendromorpha): a composite description, new samples from Western Mexico and a new species subgroup of Neotropical Cormocephalus (Cormocephalus) - Schileyko, Arkady A.; Cupul-Magaña, Fabio G. (Zootaxa, 2021)
Cormocephalus (C.) guildingii Newport, 1845—one of the oldest names in this genus—is described in detail for the first time, based on material from Western Mexico, Jamaica and the Dominican Republic; the range of this species is much expanded. Synonymy of C. impressus Porat, 1876 under C. guildingii is analyzed and confirmed. Relations between the latter and both C. ungulatus (Meinert, 1886) and C. andinus (Kraepelin, 1903) are analysed in detail. Both C. mundus Chamberlin, 1955 and C. (Cupipes) tingonus Chamberlin, 1957 are junior synonyms of C. ungulatus (Meinert, 1886). Cormocephalus mediosulcatus Attems, 1928 is suggested to be transferred to the genus Scolopendropsis as S. thayeri (Meinert, 1886) syn. nov. A new subclade (designated as the “guildingii-subgroup”) is established within the Neotropical clade of the genus Cormocephalus. It includes most Neotropical representatives of the gervaisianus species-group (sensu Schileyko & Stagl 2004) united by nine diagnostic synapomorphies. Relations within the new subclade are analysed and its diagnosis is given.